Rancangan Jaringan Highly Available PT Pundi Mas Berjaya (PMB) - Stefanus Eko Prasetyo; Gautama Wijaya; Nafisatul Hasanah; Jemmy Jemmy; Putri Syahfira (Universitas Internasional Batam, 2023)
In the digital age, networks are an important factor for implementing communication and exchanging information. Campus networks, which are private networks specifically designed for a particular institution, are essential for the institution because they provide access to the necessary information and services. However, campus networks are also vulnerable to security threats such as cybercrime and malware attacks. Firewall implementation can minimize these threats by controlling access to network services. Pundi Mas Berjaya (PMB), a company that provides software solutions to the global market, requires a highly available and redundant campus network. This research uses Cisco Packet Tracer to design and configure the network required by PMB. Implementing a highly available and redundant campus network with a hierarchical network model will improve the performance of the PMB campus network connectivity and security.